PERILAKU PICKY EATER DENGAN STATUS GIZI ANAK USIA PRASEKOLAH - Simamora, Marthalena; Sipayung, Rosetty; Sipayung, Normi Parida; Bernadet Sarni (Jurnal Online Keperawatan Indonesia, 2024)
Picky eater is a condition that refers to behavior that only wants to consume certain foods and does not want to try new foods. Nutritional status is a condition that arises from the body's need for calories and other nutrients, obtained from food intake. The aim of this study is to find out how the behavior of a picky eater relates to the nutritional status of preschool children in the Free Methodist Kindergarten. This type of research is correlation analysis with the Croos Sectional approach. The population in this study was mothers and children, the sample in the study was 68 people using total sampling techniques. The tool used is the Child Eating Behavior Questionnaire (CEBQ) questionnaire and nutritional status data from z-score with BB/TB measurement. The majority of children with picky-eater behavior were 79.4 per cent, nutritional status (n=68) and normal nutrition status was 64.7 per cent. Children with picky-eaters were mostly normal, while children who did not have picky eating behaviors were under-nutritional and poor nutritional. It was concluded that it showed that there was a relationship between picky-eater behavior and preschool child nutritional status in the Free Methodist Kindergarten (p value = 0,005). The advice in this study is expected to help the mother in paying attention to nutritional needs and improving the child's diet so that the child grows optimally.